2020
DOI: 10.3390/genes11040436
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Transcriptome Assembly and Annotation of Liver and Brain Tissues of Common Brushtail Possums (Trichosurus vulpecula) in New Zealand: Transcriptome Diversity after Decades of Population Control

Abstract: The common brushtail possum (Trichosurus vulpecula), introduced from Australia in the mid-nineteenth century, is an invasive species in New Zealand where it is widespread and forms the largest self-sustained reservoir of bovine tuberculosis (Mycobacterium bovis) among wild populations. Conservation and agricultural authorities regularly apply a series of population control measures to suppress brushtail possum populations. The evolutionary consequence of more than half a century of intensive population control… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Parallel studies were reported in Vatica mangachapoi (Tang et al 2022 ), Hopea hainanensis (Huang et al 2022 ), Neesia altissima (Pratiwi et al 2022 ), C. capsularis (Satya et al 2017 ), Hibiscus hamabo siebold & zuccarini (Wang et al 2021 ), Abelmoschus esculentus (Nieuwenhuis et al 2021 ), Helicoverpa armigera (de la Paz Celorio-Mancera et al 2011 ), Gasterophilus nasalis (Zhang et al 2021 ), and Operculina turpethum (Biswal et al 2021 ). Additionally, GAEV was used to annotate the KO (Iacobas et al 2019 ; Emami-Khoyi et al 2020 ; Nand et al 2020 ; Shah et al 2021 ). The biological process (382), with the highest level of involvement in the functional enrichment analysis results is highlighted here by GO ID and p-value.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel studies were reported in Vatica mangachapoi (Tang et al 2022 ), Hopea hainanensis (Huang et al 2022 ), Neesia altissima (Pratiwi et al 2022 ), C. capsularis (Satya et al 2017 ), Hibiscus hamabo siebold & zuccarini (Wang et al 2021 ), Abelmoschus esculentus (Nieuwenhuis et al 2021 ), Helicoverpa armigera (de la Paz Celorio-Mancera et al 2011 ), Gasterophilus nasalis (Zhang et al 2021 ), and Operculina turpethum (Biswal et al 2021 ). Additionally, GAEV was used to annotate the KO (Iacobas et al 2019 ; Emami-Khoyi et al 2020 ; Nand et al 2020 ; Shah et al 2021 ). The biological process (382), with the highest level of involvement in the functional enrichment analysis results is highlighted here by GO ID and p-value.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies were reported in Hevea brasiliensis (Li et al 2012 ), Ipomoea batatas (Wang et al 2010 ; Xie et al 2012 ), Solanum trilobatum (Lateef et al 2018 ), Gasterophilus nasalis (Zang et al 2021 ), Operculina turpethum (Biswal et al 2021 ) and Juglans mandshurica (Yan et al 2021 ). Importantly, the KO was also annotated through GAEV; hence, pathways with their number of associated genes were also obtained (Iacobas et al 2019 ; Emami-Khoyi et al 2020 ; Nand et al 2020 ; Shah et al 2021 ). Here, the functional enrichment analysis of the genes were done through g:Profiler, where the results characterized into GO ID and p-value with highest involved in the biological process (337), followed by cellular component (99) and molecular function (67).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from each specimen using a combination of mechanical homogenization with Trizol and Qiagen RNeasy purification kit (Qiagen, Hilden, Germany). Then, cDNA libraries were constructed, indexed separately (Emami-Khoyi et al 2020), and sequenced on an Illumina HiSeq TM 4000 platform (Illumina Inc., San Diego, USA) following the manufacturer's instructions for 150 bp paired-end chemistry.…”
Section: Differential Gene Expression Analysesmentioning
confidence: 99%